2018
DOI: 10.20892/j.issn.2095-3941.2017.0107
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity phosphatase 6 (DUSP6): a review of its molecular characteristics and clinical relevance in cancer

Abstract: Mitogen-activated protein kinases (MAPKs) are the main regulators of cellular proliferation, growth, and survival in physiological or pathological conditions. Aberrant MAPK signaling plays a pivotal role in carcinogenesis, which leads to development and progression of human cancer. Dual-specificity phosphatase 6 (DUSP6), a member of the MAPK phosphatase family, interacts with specifically targeted extracellular signal-regulated kinase 1/2 via negative feedback regulation in the MAPK pathway of mammalian cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 114 publications
(169 reference statements)
0
41
0
Order By: Relevance
“…It has been demonstrated that MEK variants can contribute to resistant phenotype of melanoma cells, as (i) cells harboring MEK2 F57C substitution exerted phospho-MEK2 low /phospho-ERK1/2 high signature [85], (ii) regrowth of melanoma after initial response to MEK inhibitor has been attributed to MEK1 P124L variant [86], and (iii) untreated patients harboring MEK1 P124S or MEK1 P124L variants faced rapid progression upon administration of BRAF inhibitor [13]. Another way to keep ERK1/2 active is to alter the activity of DUSP6, a specific phosphatase of ERK1/2 [87,88]. While inverse association between the levels of p-ERK1/2 and DUSP6 was found in drug-naïve cells [23], DUSP6 suppression in resistant cells was not consistently associated with an increase in phospho-ERK1/2 level, suggesting that downregulation of DUSP6 was not the only mechanism reactivating ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MEK variants can contribute to resistant phenotype of melanoma cells, as (i) cells harboring MEK2 F57C substitution exerted phospho-MEK2 low /phospho-ERK1/2 high signature [85], (ii) regrowth of melanoma after initial response to MEK inhibitor has been attributed to MEK1 P124L variant [86], and (iii) untreated patients harboring MEK1 P124S or MEK1 P124L variants faced rapid progression upon administration of BRAF inhibitor [13]. Another way to keep ERK1/2 active is to alter the activity of DUSP6, a specific phosphatase of ERK1/2 [87,88]. While inverse association between the levels of p-ERK1/2 and DUSP6 was found in drug-naïve cells [23], DUSP6 suppression in resistant cells was not consistently associated with an increase in phospho-ERK1/2 level, suggesting that downregulation of DUSP6 was not the only mechanism reactivating ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…DUSP1 , DUSP6 and LOC102190323 ). Gene DUSP is involved in the suppression of tumorigenic cell proliferation [ 59 ], a consequence of decreased cellular proliferation caused by the mammary gland involution. Gene LOC102190323 is involved in DNA damage response [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research has demonstrated that DUSPs serve as tumor suppressors or oncogenes by regulating cell proliferation, migration and apoptosis ( 12 14 ), which ultimately influences and determines the fate of specific types of cancer ( 19 ). A previous study demonstrated that DUSP1 was tightly associated with a glucose metabolism disorder and glomerular apoptosis via interrupting JNK-mitochondrial fission factor-mitochondrial fission, reducing hyperglycemia-regulated mitochondrial damage and improving renal function ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…DUSPs have been reported to mediate cell proliferation, migration and apoptosis ( 12 14 ). Accumulating evidence has demonstrated that DUSP6 serves a role in multiple types of cancer, such as glioblastoma, breast cancer and pancreatic cancer, where it displays either an oncogenic or tumor-suppressive function ( 15 18 ), which ultimately affects and determines the fate of a specific cancer ( 19 ). Another previous study suggested that DUSP6 inhibition enhanced T cell-modulated immunity in end-stage renal disease ( 20 ).…”
Section: Introductionmentioning
confidence: 99%